Diastolic Ventricular Interaction in Heart Failure With Preserved Ejection Fraction - Parasuraman, Sathish K. (J Am Heart Assoc, 2019)
BACKGROUND: Exercise‐induced pulmonary hypertension is common in heart failure with preserved ejection fraction (HFpEF). We hypothesized that this could result in pericardial constraint and diastolic ventricular interaction in some patients during exercise. METHODS AND RESULTS: Contrast stress echocardiography was performed in 30 HFpEF patients, 17 hypertensive controls, and 17 normotensive controls (healthy). Cardiac volumes, and normalized radius of curvature (NRC) of the interventricular septum at end‐diastole and end‐systole, were measured at rest and peak‐exercise, and compared between the groups. The septum was circular at rest in all 3 groups at end‐diastole. At peak‐exercise, end‐systolic NRC increased to 1.47±0.05 (P<0.001) in HFpEF patients, confirming development of pulmonary hypertension. End‐diastolic NRC also increased to 1.54±0.07 (P<0.001) in HFpEF patients, indicating septal flattening, and this correlated significantly with end‐systolic NRC (ρ=0.51, P=0.007). In hypertensive controls and healthy controls, peak‐exercise end‐systolic NRC increased, but this was significantly less than observed in HFpEF patients (HFpEF, P=0.02 versus hypertensive controls; P<0.001 versus healthy). There were also small, non‐significant increases in end‐diastolic NRC in both groups (hypertensive controls, +0.17±0.05, P=0.38; healthy, +0.06±0.03, P=0.93). In HFpEF patients, peak‐exercise end‐diastolic NRC also negatively correlated (r=−0.40, P<0.05) with the change in left ventricular end‐diastolic volume with exercise (ie, the Frank‐Starling mechanism), and a trend was noted towards a negative correlation with change in stroke volume (r=−0.36, P=0.08). CONCLUSIONS: Exercise pulmonary hypertension causes substantial diastolic ventricular interaction on exercise in some patients with HFpEF, and this restriction to left ventricular filling by the right ventricle exacerbates the pre‐existing impaired Frank‐Starling response in these patients.